Echocardiographic assessment of right ventricular function status in children with congenital heart disease with irreversible and reversible pulmonary hypertension compared to normal children - Islam, M. Tariqul; Yadav, Hira Nand; Karim, Tahmina; Alam, Mohammad S.; Barua, Chaity (International Journal of Contemporary Pediatrics, 2024)
Background: Right ventricular (RV) dysfunction is prevalent in children with congenital heart disease (CHD), particularly in association with pulmonary hypertension (PH). Transthoracic echocardiography (TTE) is crucial for detecting, assessing severity, and monitoring CHD patients with PH. The current study aimed to compare RV function assessed by TTE between CHD patients with PH and healthy children. Methods: The case group comprised CHD patients diagnosed with PH via TTE and confirmed by cardiac catheterization. The control group included children with normal echocardiograms. A total of 40 patients were enrolled based on predefined criteria. Results: The study included 20 cases and 20 controls. Echocardiographic parameters revealed significant differences between the case and control groups, with increased RV dimensions in the case group, except for RV subcostal wall thickness. RV systolic function parameters, including tricuspid annular plane systolic excursion (TAPSE) and tricuspid annular systolic velocity (S’), were significantly lower in the case group. RV diastolic function parameters, including E/A ratio, E/e’, and deceleration time (DT), were also significantly different between the groups. The RV global function parameter, tissue Doppler imaging-derived myocardial performance index (TD MPI), was significantly higher in the case group. Conclusions: Echocardiographic evaluation of RV function, including TAPSE, S’, TD MPI, E/A ratio, E/e’, and DT, in CHD children with PH correlates with PH severity. This assessment can aid in early detection of PH severity before irreversible changes occur and serve as an alternative to right heart catheterization.